Highlights on polymeric micelles as versatile nanocarriers for drug transporting - Hussein A. Abdul Hussein; Nidhal K. Maraie (College of Pharmacy / Mustansiriyah University, 2022)
Polymeric micelles are nanoscale core-shell structures formed by amphiphilic (block or graft) copolymers, that can self-aggregate in an aqueous medium. PMs characterized by small size, spherical shape, lower critical micellar concentration, which gave higher stability for PMs over conventional surfactant micelles. The core/shell structure permits polymeric micelle to entrap poor soluble drugs and can improve their solubility and permeability. The preparation of PMs tends to be relatively easy as compared to other novel drug delivery systems. This review focus on the general properties, types, types of copolymer utilized, formation mechanism, preparation methods, characterization techniques, and the applications on PMs.